35th AIAA Applied Aerodynamics Conference 2017
DOI: 10.2514/6.2017-3044
|View full text |Cite
|
Sign up to set email alerts
|

A Sweeping Jet Application on a High Reynolds Number Semi-Span Supercritical Wing Configuration

Abstract: The FAST-MAC circulation control model was modified to test an array of unsteady sweeping-jet actuators at realistic flight Reynolds numbers in the National Transonic Facility at the NASA Langley Research Center. Two types of sweeping jet actuators were fabricated using rapid prototype techniques, and directed over a 15% chord simple-hinged flap. The model was configured for low-speed high-lift testing with flap deflections of 30° and 60°, and a transonic cruise configuration having a 0° flap deflection. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Six actuators, spaced 3.3 cm apart, were in each SLA flap section. In preparation for a high Reynolds number AFC experiment, 16 this SWJ actuator configuration was previously used to e↵ectively control separation 4 at flap deflection angles up to 40 . Unlike the experiments described in Refs.…”
Section: Afc Actuatorsmentioning
confidence: 99%
“…Six actuators, spaced 3.3 cm apart, were in each SLA flap section. In preparation for a high Reynolds number AFC experiment, 16 this SWJ actuator configuration was previously used to e↵ectively control separation 4 at flap deflection angles up to 40 . Unlike the experiments described in Refs.…”
Section: Afc Actuatorsmentioning
confidence: 99%
“…Koklu and Owens [16] experimentally compared various flow control Energies 2021, 14, 4342 2 of 17 methods for flow on a ramp and confirmed that the fluidic oscillators were most effective in reducing the flow separation. Jones et al [17] studied the flow separation control on a highlift wing. Under the same conditions, fluidic oscillators showed similar lift performance with only 54% less mass flow rate compared with steady jet actuators.…”
Section: Introductionmentioning
confidence: 99%
“…1, right side) that matches the performance of a conventional Fowler flap system, while minimizing the weight and power requirements of the AFC system. Pneumatic-powered AFC concepts, such as steady blowing through discrete convergent-divergent nozzles [6] or unsteady blowing through fluidic oscillators (often referred to as sweeping jet actuators) [8][9][10][11][12][13][14][15][16][17][18][19], have been investigated around the flap shoulder region during the course of this project.…”
Section: Introductionmentioning
confidence: 99%
“…For this configuration, the lift increased monotonically with increasing NPR, although the slope of the lift curve was reduced for NPR>2.0, as reported in Figs. (17)(18) of Ref. [20].…”
Section: Introductionmentioning
confidence: 99%